The Early Work (1916-1938) of Austin Clarke - Riordan, Maurice (My University, 1981)
Austin Clarke dedicated himself to the ideal of an independent Irish literature in English. This dedication had two principal consequences for his work: he developed a poetic style appropriate to expressing the Irish imagination, and he found inspiration in the matter of Ireland, in hex mythology and folklore, in her literary, artistic and religious traditions, and in the daily life of modern Ireland. The basic orientation of Clarke's work determines the twofold purpose of this thesis. It seeks to provide a clarifying background for his poetry, drama and fiction up to 1938; and, in examining the texts in their proper context, it seeks to reveal the permanent and universal aspects of his achievement. Clarke's early development in response to the shaping influence of the Irish Revival is examined in the opening chapter. His initial interest in heroic saga is considered, but, principally, the focus is on his effort to establish stylistic links between the Anglo-Irish and the Gaelic traditions, an effort that is seen to culminate with his adoption of assonantal verse as an essential element in his poetic technique. In the second chapter, the emphasis shifts to the thematic consequences of Clarke's involvement with Ireland. His understanding of Irish tradition is discussed, and, in particular, the origins and nature of his imaginative preoccupation with the culture of early Christian Ireland are examined. What emerges is that Clarke perceives a permanent tension in the Irish mind between the Christian and the pagan viewpoints, a conflict of values that he termed the drama of conscience. The conflict informs each of the major texts analysed in the remainder of the thesis. Pilgrimage and Other Poems, discussed in the second chapter, reveals the recurrence of the tension between the Christian and the pagan traditions in the course of Irish history. Clarke's early plays and novels, which are the focus of the third chapter, relate the conflict to the culture of medieval Ireland. The fourth chapter examines Clarke's own experience cf the conflict as it is presented in Night and Morning. In the recognition that the drama of conscience remains a vital element in Clarke's imagination after 1938, the thesis concludes by indicating the main lines of continuity between the earlier and the later work.
Keywords: austin clarke; early work; 1916; 1938